Effects of Recreational Noise on Threshold and Suprathreshold Measures of Auditory Function - Fulbright, Angela N.C.; Le Prell, Colleen G.; Griffiths, Scott K.; Lobarinas, Edward (Seminars in Hearing, 2017)
Noise exposure that causes a temporary threshold shift but no permanent threshold shift can cause degeneration of synaptic ribbons and afferent nerve fibers, with a corresponding reduction in wave I amplitude of the auditory brainstem response (ABR) in animals. This form of underlying damage, hypothesized to also occur in humans, has been termed synaptopathy, and it has been hypothesized that there will be a hidden hearing loss consisting of functional deficits at suprathreshold stimulus levels. This study assessed whether recreational noise exposure history was associated with smaller ABR wave I amplitude and poorer performance on suprathreshold auditory test measures. Noise exposure histories were collected from 26 men and 34 women with hearing thresholds ≤ 25 dB hearing loss (HL; 250 Hz to 8 kHz), and a variety of functional suprathreshold hearing tests were performed. Wave I amplitudes of click-evoked ABR were obtained at 70, 80, 90, and 99 dB (nHL) and tone-burst evoked ABR were obtained at 90 dB nHL. Speech recognition performance was measured in quiet and in competing noise, using the Words in Noise test, and the NU-6 word list in broadband noise (BBN). In addition, temporal summation to tonal stimuli was assessed in quiet and in competing BBN. To control for the effects of subclinical conventional hearing loss, distortion product otoacoustic emission amplitude, an indirect measure of outer hair cell integrity, was measured. There was no statistically significant relationship between noise exposure history scores and ABR wave I amplitude in either men or women for any of the ABR conditions. ABR wave I amplitude and noise exposure history were not reliably correlated with suprathreshold functional hearing tests. Taken together, this study found no evidence of noise-induced decreases in ABR wave I amplitude or signal processing in noise in a cohort of subjects with a history of recreational noise exposure.
Keywords: Hidden hearing loss; speech in noise; noise exposure history; ABR wave I amplitude; and temporal summation